Hazard Assessment of Benchmark Metal-Based Nanomaterials Through a Set of In Vitro Genotoxicity Assays - Vital, Nádia (2022)
For safety assessment of nanomaterials (NMs), in vitro genotoxicity data based on welldesigned experiments is required. Metal-based NMs are amongst the most used in consumer products. In this chapter, we report results for three metal-based NMs, titanium dioxide (NM- 100), cerium dioxide (NM-212) and silver (NM-302) in V79 cells, using a set of in vitro genotoxicity assays covering different endpoints: the medium-throughput comet assay and its modified version (with the enzyme formamidopyrimidine DNA glycosylase, Fpg), measuring DNA strand beaks (SBs) and oxidized purines, respectively; the micronucleus (MN) assay, assessing chromosomal damage; and the Hprt gene mutation test. The results generated by this test battery showed that all NMs displayed genotoxic potential. NM-100 induced DNA breaks, DNA oxidation damage and point mutations but not chromosome instability. NM-212 increased the level of DNA oxidation damage, point mutations and increased the MN frequency at the highest concentration tested. NM-302 was moderately cytotoxic and induced gene mutations, but not DNA or chromosome damage. In conclusion, the presented in vitro genotoxicity testing strategy allowed the identification of genotoxic effects caused by three different metal-based NMs, raising concern as to their impact on human health. The results support the use of this in vitro test battery for the genotoxicity assessment of NMs, reducing the use of more expensive, time-consuming and ethically demanding in vivo assays, in compliance with the 3 R’s.